Health education with Characteristics of Traditional Chinese Medicine for patients with knee osteoarthritis (膝骨关节炎的中医特色健康教育) - LI Suqian (李苏茜); TANG Ling (唐玲); LI Ye (李野) (Association of Integrative Nursing, 2021)
In order to promote the development of clinical nursing work in medical institutions of Traditional Chinese Medicine(TCM), highlight the characteristics and advantages of TCM nursing, and make the innovation and development of TCM nursing in inheritance, under the guidance of Beijing Administration of TCM, Beijing Office of TCM Nursing Ability Improvement Project launched the construction project of "One Syndrome and One Product" specialized nursing demonstration ward in October 2017. In November 2020, the Department of Rheumatology set up a project of "One Syndrome and One Product" for patients with knee osteoarthritis, and carried out a one-year project construction. In the process of implementation, the connotation of nursing service were deepened and expanded, giving full play to the characteristic role of TCM nursing service and providing better nursing service for patients. This paper summarized the health education service system with TCM characteristics, and summarized the problems existing in the implementation process. (为了促进全市中医医疗机构临床护理工作的发展, 突出中医护理的特色与优势, 使中医护理在继承中创新发展, 在北京市中医管理局的指导下, 北京市中医护理能力提升工程办公室于2017年10月开展"一证一品"专科护理示范病房建设项目。风湿科于2020年11月对膝骨关节炎疾病进行了"一证一品"院内立项, 进行为期1年的项目建设, 在全面实施过程中科室对护理服务内涵深入化、扩大化, 充分发挥中医护理在中医药服务中的特色作用, 为患者提供更优质的护理服务。本文对中医特色健康教育服务体系予以综述, 并对实施过程中存在的问题进行了总结。)